Acute Myocardial Infarction Due to Dissection of the Coronary Arteries Associated with Premature Atherosclerosis in Late Postpartum: A Case Report of Maternal Death - Vaseghi, Fatemeh; Rajabi Moghaddam, Hasan; nasiri, saeideh; Moravveji, Alireza; Foroozanfard, Fatemeh (Advances in Nursing & Midwifery, 2021)
Abstract Introduction: Atherosclerotic coronary artery disease is the most common form of heart disease that is associated with high rates of acute myocardial infarction (AMI) and death in young people. Methods: Given the importance of pregnancy and the postpartum period and the fact that AMI is associated with poor maternal outcomes in postpartum, the present study reports acute myocardial infarction due to dissection of the coronary arteries associated with premature atherosclerosis in late postpartum. Results: The case was the maternal death of a 34-year-old woman at 42 days postpartum without any history of underlying diseases or symptoms, whose autopsy report read AMI due to coronary artery dissection associated with atherosclerosis. Conclusions: This report emphasizes the importance of postpartum care and attention to any symptoms witnessed during this period.